Effect of applying a developed nursing program on activities of daily living among elderly residing in nursing homes in Lattakia (Journal of Hama University, 2026)
Introduction: The ability to perform activities of daily living (ADL) declines in most older adults as they age. This leads to reduced quality of life, dependence on others for activities of daily living (ADLs), and increased healthcare costs. All activities of daily living (ADLs), with the exception of mobility, rely on skilled hand movement. Therefore, for older adults, maintaining hand function is essential for independent living. Given that proficiency in ADLs is largely dependent on healthy hand function, research on improving hand function has the potential to contribute to prevention or intervention strategies to help maintain functional independence in older adults.Objective: To study the impact of implementing an advanced nursing program on the performance of daily living activities among elderly residents of nursing homes in Lattakia.Research Materials and Methods: A quasi-experimental study was conducted after determining the appropriate sample size for the research, which is 30 elderly people who were selected randomly from the elderly residing in nursing homes in the city of Lattakia (Dar Al Raha, Dar Al Ber and Social Services, Dar Al Mowasat Al Islamiya) during the period from (1/5/2024 to 1/12/2024). Data were collected using two tools: the demographic and health data form for the elderly, which was designed by the researcher based on a review of relevant references, and the Barthel Index to measure daily living activities. The data were transcribed and then analyzed using the Statistical Package for the Social Sciences (SPSS).Results: The results showed an improvement in the Barthel Index scores after implementing the advanced nursing program, with statistically significant differences found between the pre-, post-, and follow-up tests for activities of daily living.Recommendations: It is recommended to conduct training programs for elderly residents of nursing homes to enhance their hand function, prevent decline, and maintain their independence in performing daily activities, as well as to implement hand motor rehabilitation programs.
Keywords: effect; training program; activity of daily living; elderly people; nursing home